Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

simplify fully...

x²+3x-4 / 2x²-5x+3


Sagot :

=x²+3x-4/2x²-5x+3
=(x-1)(x+4)/½(2x-2)(2x-3)
=---------------------------
AyaZ
[tex] \frac{ x^{2} +3x-4 }{ 2 x^{2} -5x+3} = \frac{(x+4)(x-1)}{(x-1)(2x-3)} = \frac{x+4}{2x-3} [/tex]